Concurrent analysis of hospital stay durations and mortality of emerging severe acute respiratory coronavirus virus 2 (SARS-CoV-2) variants using real-time electronic health record data at a large German university hospital - Derek Y. Hazard; Marlon Grodd; Adeline Makoudjou; Sara Lozano; Andrea Prunotto; Patric Tippmann; Daniela Zöller; Philipp Mathé; Siegbert Rieg; Martin Wolkewitz (Antimicrobial Stewardship & Healthcare Epidemiology, 2023)
Multistate methodology proves effective in analyzing hospitalized coronavirus disease 2019 (COVID-19) patients with emerging variants in real time. An analysis of 2,548 admissions in Freiburg, Germany, showed reduced severity over time in terms of shorter hospital stays and higher discharge rates when comparing more recent phases with earlier phases of the pandemic.